2020
DOI: 10.3889/oamjms.2020.5249
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease-19 Lockdown on Egyptian Children and Adolescents: Dietary Pattern Changes Health Risk

Abstract: BACKGROUND: Lockdown and school closure related to the coronavirus disease 2019 (COVID-19) have unfavorable effects on children and adolescents. AIM: This study was conducted to survey the changes in dietary pattern and related health factors in Egyptian children and adolescents during the COVID-19 outbreak closure. MATERIALS AND METHODS: Data were collected through a dietary pattern, eating behavior, and physical activity electronic questionnaire conducted through social media sites, targeting par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
5
22
1
Order By: Relevance
“…Our findings regarding the adult groups are consistent with similar studies. A similar study found that the longer the duration of internet use among Egyptian children and adolescents during COVID−19, the more likely they were to reduce their intake of vegetables, fruits, or protein ( 82 ). The Instagram Social Network can influence adolescents' eating behaviors ( 83 ) and shape eating trends ( 84 ).…”
Section: Resultsmentioning
confidence: 97%
“…Our findings regarding the adult groups are consistent with similar studies. A similar study found that the longer the duration of internet use among Egyptian children and adolescents during COVID−19, the more likely they were to reduce their intake of vegetables, fruits, or protein ( 82 ). The Instagram Social Network can influence adolescents' eating behaviors ( 83 ) and shape eating trends ( 84 ).…”
Section: Resultsmentioning
confidence: 97%
“…This result echoes a study that found that longer sleep time changed daily eating habits among the Croats during the pandemic [ 72 ]. In contrast, another study has indicated that a reduction in sleep time significantly increases dietary change patterns [ 73 ]. To ensure a better lifestyle and dietary behavior during the pandemic, it is essential to provide information regarding COVID-19 and healthy lifestyle via the internet and health associates to the masses and to communities 74 , 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings revealed that changes in eating patterns were found in Egyptian children and adolescents. 45.6 % of the participants reported increased sweets and unhealthy food consumption, and 37.6% showed increased frequent snacking between meals [9].…”
Section: Impact Of Covid-19 Lockdown On Dietary Patternmentioning
confidence: 98%